The geographic distribution of big five personality traits: patterns and profiles of human self-description across 56 nations - Schmitt, David P. (2007)
The Big Five Inventory (BFI) is a self-report measure designed to assess the high-order personality traits of Extraversion, Agreeableness, Conscientiousness, Neuroticism, and Openness. As part of the International Sexuality Description Project, the BFI was translated from English into 28 languages and administered to 17,837 individuals from 56 nations. The resulting cross-cultural data set was used to address three main questions: Does the factor structure of the English BFI fully replicate across cultures? How valid are the BFI trait profiles of individual nations? And how are personality traits distributed throughout the world? The five-dimensional structure was robust across major regions of the world. Trait levels were related in predictable ways to self-esteem, sociosexuality, and national personality profiles. People from the geographic regions of South America and East Asia were significantly different in openness from those inhabiting other world regions. The discussion focuses on limitations of the current data set and important directions for future research.